Online interprofessional education in dietetic students. Issue 3 (2nd November 2015) - Evans, Sherryn; Ward, Catherine; Margerison, Claire
Abstract: Aim: The need for dietetic students to develop interprofessional collaborative practice capabilities is well recognised. The aim of this study was to examine the ability of an online interprofessional education (IPE) unit (using asynchronous and synchronous media) to improve dietetic students' confidence in understanding professional roles and attitudes associated with interprofessional practice along with exploring their experience in the unit. Methods: Final year master of dietetic students undertaking a compulsory online unit in IPE were invited to complete a questionnaire examining their confidence in understanding professional roles and their interprofessional attitudes both pre‐ and post‐delivery of the unit, and to participate in semi‐structured telephone interviews to explore their experience in the unit. Results: Thirty‐five dietetic students completed the questionnaire pre‐ and post‐unit, along with seven students undertaking a telephone interview. Their confidence in understanding the roles of other health professions ( P = 0.000 to 0.014), self‐assessment of interprofessional communication and teamwork skills ( P = 0.002) and attitudes towards interprofessional interaction ( P = 0.001) and interprofessional relationships ( P = 0.002) increased significantly from pre‐ to post‐unit. The students articulated positives about the experience (flexibility of the delivery, opportunity to reflect on personal factors related to teamwork, increasing their knowledge of other professions) and some challenges (lack of body language, some technological difficulties, the need for regular contribution to the teams' asynchronous discussion boards). Conclusions: This study suggests that although there can be some challenges in online IPE, it can be a positive experience and can improve dietetic students' collaborative practice attitudes and confidence in understanding other professional roles.